2017
DOI: 10.1155/2017/7539735
|View full text |Cite|
|
Sign up to set email alerts
|

Subclinical Hypothyroidism and Its Association with Increased Cardiovascular Mortality

Abstract: Thyroid hormones play an important role in regulating different metabolism functions and multiple organs' performance. Changes in the thyroid hormone axis can lead to profound effects on the stability of vital organs and systems, especially the cardiovascular system. Hypothyroidism is classified according to the clinical presentation as overt and subclinical. There is some evidence supporting the benefits of thyroxine hormone replacement for subclinical hypothyroidism on cardiovascular mortality outcomes. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Our study also shows that T3 and FT3 levels do not predict adverse cardiovascular outcomes in AMI patients. There is conflicting evidence regarding thyroid hormone levels and cardiovascular outcomes [2426]. It has been reported that thyroid function tests predict disability in advanced old age patients, with higher serum TSH levels predicting better outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also shows that T3 and FT3 levels do not predict adverse cardiovascular outcomes in AMI patients. There is conflicting evidence regarding thyroid hormone levels and cardiovascular outcomes [2426]. It has been reported that thyroid function tests predict disability in advanced old age patients, with higher serum TSH levels predicting better outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that thyroid function tests predict disability in advanced old age patients, with higher serum TSH levels predicting better outcomes [27]. Moreover, in patients with acute heart failure, subclinical hypothyroidism on admission is an independent predictor of adverse cardiovascular outcomes [24]. In this study, thyroid function is not associated with all-cause mortality and MACE in AMI patients over a 2-year follow-up, indicating that the interaction between T3 and cardiac function might be more significant during acute phase of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism affects all organic systems, but the most common symptoms that burden HT patients are weight gain, constipation, hoarse voice, lethargy, fatigue, cold intolerance, hair loss and dry skin (Chaker and Bianco et al, 2017). Untreated hypothyroidism results with severe consequences on human health, but today there is more evidence that even subclinical hypothyroidism may have adverse effects on health (Altamirano Ufion and Zulfiqar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As the symptoms of hypothyroidism may be non-specific, appropriate thyroid hormone levels monitoring in patients who have undergone RT in the head and neck region is of great importance. Inadequate levels of thyroid hormones negatively impact the patients’ quality of life [ 8 ], their morbidity and mortality [ 5 , 9 , 10 , 11 ]; even subclinical hypothyroidism (elevated TSH with normal T3 and T4) contributes significantly to increased cardiovascular mortality [ 12 ]. Hypothyroidism symptoms and the risk it incurs may be reversed with thyroid hormone replacement, mandating routine follow-up of thyroid function and considering the thyroid gland as an organ at risk (OAR) during RT treatment planning.…”
Section: Introductionmentioning
confidence: 99%